Cephalosporin and Ciprofloxacin Resistance in Salmonella, Taiwan - Jing-Jou Yan; Chien-Shun Chiou; Tsai-Ling Yang Lauderdale; Shu-Huei Tsai; Jiunn-Jong Wu (Emerging Infectious Diseases, 2005)
We report the prevalence and characteristics of Salmonella strains resistant to ciprofloxacin and extended-spectrum cephalosporins in Taiwan from January to May 2004. All isolates resistant to extended-spectrum cephalosporins carried blaCMY-2, and all ciprofloxacin-resistant Salmonella enterica serotype Choleraesuis isolates were genetically related.